Pengaruh Disrupsi Rantai Pasok Global terhadap Kinerja Keuangan Perusahaan Manufaktur di Indonesia dengan Manajemen Persediaan sebagai Variabel Mediasi (Periode 2020–2024) - Tomy Mandala Putra; Andry Arifian Rachmat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the effect of global supply chain disruption, proxied by lead time, on the financial performance of textile manufacturing companies in Indonesia, with inventory management, proxied by inventory turnover, as a mediating variable over the 2020–2024 period. The study uses a quantitative explanatory approach with panel data from four production units, analyzed using the Fixed Effect Model in EViews 13 and a Sobel test for mediation. The results show that lead time has no significant effect on financial performance (ROA) nor on inventory management, while inventory turnover has a positive and significant effect on financial performance. Inventory management does not mediate the relationship between supply chain disruption and financial performance. The findings reinforce the Resource-Based View, indicating that internal resource management plays a more decisive role than lead time changes in maintaining corporate financial performance.